The uncertainty associated with visual flow fields and their influence on postural sway: Weber’s law suffices to explain the nonlinearity of vection - Wei, Kunlin (2010)
When we stand upright, we integrate cues from multiple senses, such as vision and proprioception, to maintain and regulate our vertical posture. How these cues are combined has been the focus of a range of studies. These studies generally measured how subjects deviate from standing upright when confronted with a moving visual stimulus displayed in a virtual environment. Previous research had shown that uncertainty is central in such cue combination problems. Here we wanted to understand, quantitatively, how visual flow fields and uncertainty about them affect human posture. To do so, we combined experimental methods from perceptual psychophysics with methods from motor control studies. We used a two-alternative forced-choice paradigm to measure uncertainty as a function of the magnitude of a random-dot flow field and stimulus coherence. We subsequently measured movement amplitude as a function of visual stimulus parameters. In line with previous research, we find that sensorimotor behavior depends nonlinearly on the stimulus amplitude and, importantly, is affected by uncertainty. We find that this nonlinearity and uncertainty dependence is accurately predicted by standard Bayesian cue combination. Importantly, a Weber’s law where visual uncertainty depends on stimulus amplitude is enough to explain the nonlinear behavior.